The Influence of Outpatient Service Quality and Patient Characteristics on BPJS Patient Satisfaction at Hospital X Mediated by Doctor-Patient Relationship - Adinda, Havivi Rizky; Hendra Achmadi (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
The performance of nurses needs attention from health service providers because it can be related to the quality of health services. This study aims to analyze the effect of outpatient service quality and patient characteristics on patient satisfaction through the mediation of the doctor-patient relationship. Respondents in this study were 294 outpatients using BPJS at Hospital X. The type of research used is descriptive quantitative and was conducted at one point in time (cross sectional). The sampling technique used purposive sampling with predetermined criteria. The questionnaire was distributed online via a Google Form link that was distributed to outpatients participating in BPJS who were treated at Hospital X. This study used a multivariate analysis method with the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. This study concludes that service quality has a positive and significant effect on the doctor-patient relationship. Patient characteristics do not significantly affect the doctor-patient relationship. The doctor-patient relationship has a positive and significant effect on patient satisfaction. Service quality has a positive and significant effect on patient satisfaction mediated by the doctor-patient relationship. Patient characteristics do not significantly affect patient satisfaction through the mediation of the doctor-patient relationship. Hospitals that focus on improving the quality of their services, especially in outpatient services, will provide a positive experience for BPJS patients during treatment, as well as improve the medical and non-medical abilities of doctors. The relationship between doctors and patients is an important factor in shaping a positive patient experience during the process of providing outpatient health services in hospitals.